Vancomycin-Allergy and Linezolid-Resistance in Patient with Methicillin-Resistance Staphylococcus aureus and Multi-Drug Resistance Acinetobacter baumannii Infection - Wahyu Semara Putra Wayan; Dwita Yaniswara Ni Made; Sandy Laveda; Evelyn Nathania (Indonesian Society of Respirology (ISR), 2023)
Background: Hospital Acquired Pneumonia (HAP) has been burdening the healthcare system, especially when bacteria such as Acinetobacter baumannii and methicillin-resistance Staphylococcus aureus (MRSA) are involved. They created a dilemma regarding the appropriate antibiotic therapy utilized against them, especially when the patient is allergic/intolerant to their drug of choice. Case: A 71-year-old man developed HAP while he was admitted for an ischaemic stroke. His bronchoalveolar lavage (BAL) culture showed MRSA and Acinetobacter baumannii infection with multiple drug resistance including one of the drugs for MRSA infection, linezolid. Amikacin and vancomycin were given, but he developed an allergy to vancomycin. Due to the difficulty in treating him, we opted to administer only amikacin. His clinical condition showed daily improvement. During the last day of hospitalization, his sputum culture showed only normal flora. He no longer needed oxygen therapy and there was no longer any indication for him to be hospitalized. Conclusion: Individuals with multiple comorbidities, recent antibiotic use within the past 90 days, and immune-deficient conditions are at a higher risk of developing infections, including the possibility of dual infections. In this case, we found that the patient was unable to tolerate first-line drugs for MRSA like linezolid and vancomycin, which makes it difficult to decide upon effective treatments.